Implementasi Profesionalisme Tenaga Pendidik Dalam Upaya Meningkatkan Mutu Pembelajaran - Aji Pramudya; Amaluddin Tanjung; Elsa Hasibuan; Imas Ayu Salamah; Nindya Azzahrah; Nur Khotima; Tri Suci Apriani Harahap (Jurnal Ilmiah Wahana Pendidikan, 2022)
Professionalism to the demands of each profession. Without exception the teaching profession who daily deal with the nation’s future children with a variety of characteristics of each are not the same. Teachers are an important component in the learning process. in improving the quality of learning, the teacher role and serves as a demonstrator, the class manager, mediator and facilitator, and evaluator. Professional teachers is important because those who have professional skills in various capacities as an educator. Teachers with keprofesionalitasnya it will be able to improve the learning process so as to improve the quality of learning.